The main principles guided the evolution of positions in the evolutionary modeling of complex technical problems of system - Климова, К. Ю. (Problems of Informatization and Control, 2010)
The approach of evolutionary modeling to create adaptive management on natural bases in the prob-lem of managing complex engineering systems. The basic principles of modeling guided evolution, the basic elements of the system, the basic properties of system elements, the notion of coevolution model